The fourth dimension: physiological resilience as an independent determinant of endurance exercise performance - Jones, A. M. (Journal of Physiology, 2024)
Endurance exercise performance is known to be closely associated with the three physiological pillars of maximal O2 uptake (VO2max), economy or efficiency during submaximal exercise, and the fractional utilisation of VO2max (linked to metabolic/lactate threshold phenomena). However, while `start line` values of these variables are collectively useful in predicting performance in endurance events such as the marathon, it is not widely appreciated that these variables are not static but are prone to significant deterioration as fatiguing endurance exercise proceeds. For example, the `critical power` (CP), which is a composite of the highest achievable steady-state oxidative metabolic rate and efficiency (O2 cost per watt), may fall by an average of 10% following 2 h of heavy intensity cycle exercise. Even more striking is that the extent of this deterioration displays appreciable inter-individual variability, with changes in CP ranging from <1% to ~32%. The mechanistic basis for such differences in fatigue resistance or `physiological resilience` are not resolved. However, resilience may be important in explaining superlative endurance performance and it has implications for the physiological evaluation of athletes and the design of interventions to enhance performance. This article presents new information concerning the dynamic plasticity of the three `traditional` physiological variables and argues that physiological resilience should be considered as an additional component, or fourth dimension, in models of endurance exercise performance.